Influence of Leadership Styles on Business Model, Performance and Sustainability of Small and Medium Enterprises in India - Das, Sourabh (Global journal of Business and Integral Security, 2025)
The purpose of this research study was to identify the relationship that may exist between leadership styles, adopted business models, business performance measurement and business growth & sustainability approach of SMEs in India, and explain the factors for sustainable, value-driven and goal-oriented performance in the context of culture and values, customer centricity, and environmental and societal commitment. The final aim was to develop leadership style specific business performance framework for the SMEs. This study captured, analyzed and presented the findings of mindsets and practices of 59 SME leaders from multiple industry sectors across different parts of India through a detailed and comprehensive survey. The survey covered different types of leadership mindsets and practices along with selected dimensions of business model adoption, business performance, and business growth & sustainability. Alongside, the inter-relationship and associations between these dimensions were studied to understand how they influence the actions of these leaders. The study revealed that SME leaders give the maximum focus on Optimization parameters followed by Agility and Adaptability for Business Model adoption. Similarly, in order to formulate the approach for Business Growth and Sustainability, SME leaders have shown a stronger emphasis on the Culture & Values of the enterprise compared to Customer Centricity or Environmental Commitment. In this context, SME leaders have indicated their least attention for Societal Commitment parameters. Likewise, for Business Performance, SME leaders have shown maximum preference for Sustainable mindsets followed by Goal-Oriented and ValueDriven mindsets. Moreover, the study has shown that there are 12 key mindsets and practices of SME leaders for Business Model Adoption, and 9 key mindsets and practices, each for Business Performance, and Business Growth & Sustainability. The findings also resulted in leadership style specific business performance framework for SMEs. The outcome of this study would be useful as a guideline to understand the factors and associated mindsets to manage the challenges of growth and sustainability of a SME business. The findings demonstrate the significance of predominant leadership styles to define performance framework and non-financial performance and success indicators while being agile, adaptable, technology-driven or optimization-oriented for business model adoption. The results could be further used for focused and contextual training to new leaders to improve their effectiveness based on enterprise goals and their relationship.